Social Anxiety among Chinese People - Qianqian Fan; Weining C. Chang (The Scientific World Journal)
The experience of social anxiety has largely been investigated among Western populations; much less is known about social anxiety in other cultures. Unlike the Western culture, the Chinese emphasize interdependence and harmony with social others. In addition, it is unclear if Western constructed instruments adequately capture culturally conditioned conceptualizations and manifestations of social anxiety that might be specific to the Chinese. The present study employed a sequence of qualitative and quantitative approaches to examine the assessment of social anxiety among the Chinese people. Interviews and focus group discussions with Chinese participants revealed that some items containing the experience of social anxiety among the Chinese are not present in existing Western measures. Factor analysis was employed to examine the factor structure of the more comprehensive scale. This approach revealed an “other concerned anxiety” factor that appears to be specific to the Chinese. Subsequent analysis found that the new factor—other concerned anxiety—functioned the same as other social anxiety factors in their association with risk factors of social anxiety, such as attachment, parenting, behavioral inhibition/activation, and attitude toward group. The implications of these findings for a more culturally sensitive assessment tool of social anxiety among the Chinese were discussed.